Thermal stability of trypsin inhibitor activity in winged bean (Psophocarpus tetragonolobus) - Tan, Nget Hong; Wong, Kai Choo (American Chemical Society, 1982)
The thermal stability of trypsin inhibitor activity (TIA) in six varieties of winged beans was investigated. The TIA in winged bean meals was extremely resistant to dry heat treatment. Prolonged cooking (45–60 min) of the whole bean was required to reduce the TIA substantially. Autoclave treatment at 120 °C, 1.05 kg/cm2, is, however, very effective in destroying TIA in the beans or bean meals. There are significant varietal variations in the effectiveness of autoclave inactivation of winged bean TIA. The TIA in the winged bean meal extracts is, however, heat labile.